Arab-Jewish Conflict: An Examination of Its Origin - Abedo, Abdussalam Umar (African Journal of Stability and Development (AJSD), 2025)
The Jews believe that the land of Jerusalem is their eternal home. This belief contributed to the rise of a Zionist movement in Europe from the 1800s to the early 1900s. That movement promoted the idea of a Jewish “return” to Palestine. Later, the Law of Return established a legal basis for Jews worldwide to immigrate to and obtain citizenship in the State of Israel. It should be noted that after the British Mandate ended in 1948 and the State of Israel was established that year, there was hope that a democratic Israeli constitution would include non-Jewish citizens. That hope was thwarted as the displacement of Palestinians continued—most notably during the Nakba of 1948 and with further large-scale displacements after Hamas attacked Israel on 7th October, 2023. This paper argues that the Israeli-Palestinian crisis dates back more than 73 years and did not begin on 7th October, 2023. Essentially, the Arab-Israeli conflict has roots extending as far back as the Balfour Declaration, which led to the creation of the State of Israel in 1948. The core issue between Arabs and Jews was that Zionism, a Jewish movement, became the primary catalyst in the emotionally charged crisis of the region. The role of Western powers and the Arabs’ attitude towards the plight of the Arabs-Palestinians also intensified the ongoing turmoil. The United Nations’ attempts to resolve the conflict by proposing two neighbouring states, Palestine and Israel, failed miserably. The American President, Donald Trump’s declaration to recognise Jerusalem as the capital of Israel, and his encouragement for Egypt and Jordan to accept Gaza refugees within their borders, further inflamed Arab resentment. This paper, therefore, discusses the origin of the Arabs and Jewish conflicts in its historical unfolding and proposes some conflict resolution strategies involving pan-Arabism and the Zionist agenda within the context of Jewish Israel and the Arabs-Palestine conflict.